Women and planetary health in Asia-Pacific - Gan, Connie Cai Ru; McNamara, Caitlin; Gunasiri, Hasini; Oliva, Pats; Sebar, Bernadette (Frontiers in Climate, 2023)
In the face of climate change, women's preconceived vulnerability and virtuousness often deflect focus from gender inequality in decision-making and leadership. Within environmental, political, and social crises, women are capable and proficient leaders who are pivotal to climate change action and are already inspiring social change in innovative ways. This paper presents examples of women-led environment movements in the Asia Pacific that challenge the patriarchal notions that women must be rescued rather than actively participate in their own salvation. Historically, strategies have been centred on eco-conscious activism and organized protests. As climate change effects become more evident, engagement has transformed into emergency response and preparedness, with women groups shepherding and leveraging through healthcare settings, grassroots and community networks. The way forward is to urge meaningful policy actions to support women as effective planetary stewards and campaigners against environmental challenges. This will be achieved through funding mechanisms, gender-inclusive representation mentorships, and pathways that transcend political boundaries.